(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper examines the Russia-Ukraine war through the lens of comparative historical analysis, identifying recurring patterns in Russian imperial expansion, European responses to aggression, and the tragic repetition of diplomatic miscalculations across centuries. Drawing upon extensive scholarship, archival sources, and contemporary analysis from 2022 to 2026, this paper explores four principal historical parallels that illuminate the current conflict. First, the Crimean War (1853–1856) serves as a precursor to Russia’s contemporary strategic overreach, demonstrating how tsarist ambitions in Ottoman territories parallel Putin’s designs on Ukraine, and how both conflicts arose from anxieties about declining influence and the spread of Western ideas. Second, the paper examines the catastrophic diplomatic precedents of the Munich Agreement (1938) and the Yalta Conference (1945), drawing cautionary lessons for contemporary peace negotiations that risk sacrificing Ukrainian sovereignty for illusory stability. Third, the Budapest Memorandum (1994) is analysed as a testament to the fragility of security assurances when unaccompanied by enforceable guarantees, demonstrating how Ukraine’s voluntary nuclear disarmament was met with betrayal rather than protection. Fourth, the paper investigates Russia’s systematic weaponisation of history itself, deploying distorted historical narratives to justify aggression, deny Ukrainian statehood, and mobilise domestic support for war. Through these parallel investigations, the paper argues that while history does not literally repeat, it offers discernible patterns that, if ignored, condemn successive generations to relearn the same costly lessons. The paper concludes by considering what historical consciousness demands of the international community in responding to Russian aggression and supporting Ukrainian resistance.